The effect of chalcogen atom on the structural, elastic, and high-pressure properties of XY compounds (X=La, Ce, Eu, and Y=S, Se, and Te): An ab initio study - Charifi, Z.; Baaziz, H.; Saeed, Yasir; Ali Hussain, Reshak, Prof. Dr.; Soltani, F. (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim., 2013)
Link to publisher's homepage at http://onlinelibrary.wiley.com/